Covid-19 and Presidential Popularity in Latin America - Sosa-Villagarcia, Paolo; Hurtado Lozada, Verónica (Revista Latinoamericana de Opinión Pública, 2021)
The current pandemic challenged political leaders. As governments introduced containment policies, presidential approvals in several countries started to rise. This phenomenon brought back the discussion on the Rally-’round-the-Flag effect, which refers to the public's propensity to put aside political differences and support presidents during episodes of international crises. By focusing on four Latin American presidents, we analyze such effect and the conditions that mediate it, considering its significant variation in the region. We propose that the change in presidential popularity is short-lived and ultimately conditioned by the timing and stringency of the policy responses, the pandemic's framing, and the opposition's opportunities for policy criticism.